PERBANKAN SYARIAH DAN KONVERSI BANK KONVENSIONAL MENJADI BANK SYARIAH DITINJAU DARI HUKUM POSITIF - Syarlas, Giffari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
Efforts to accelerate the development of Sharia banking are not only carried out by the Government and the Financial Services Authority as regulators, but also need support from internal Sharia banks, as well as positive appreciation of the Indonesian people, thus making conventional banks interested in converting their bank business into sharia business. The methodology in this paper is normative juridical with the aim to examine the ideality of the concept of banking development in Indonesia, where banks operating in Indonesia are not only conventional banks but also consist of banks that have undergone sharia principles based on Islamic laws between banks and other activities. The conclusion of this paper is that conversion is reviewed from positive law, namely that Conventional commercial banks that want to turn their business activities into banks based on sharia principles must meet the provisions contained in Article 4 paragraph (1) of the Regulation of the Financial Services Authority No. 64/POJK.03/2016 concerning Changes in Business Activities of Conventional Banks into Sharia Banks, which can only be done with permission from the Financial Services Authority.